Good Urban Governance through ICT : Issues, Analysis, and Strategies - Relhan, Gaurav; Ionkova, Kremena; Huque, Rumana (World Bank, Washington, DC, 2017)
Africa is currently experiencing the world's fastest urbanization rate at 3.5 percent annually-placing increasing pressure on resource-constrained local governments to maintain and improve livability standards of their cities. But simultaneously, an 'Information and Communication Technologies' (ICT) revolution has swept across the continent-as evidenced by vastly improved telecommunications and internet infrastructure, leapfrogging mobile communications penetration rates, and emergence of a successful homegrown IT applications industry. This report aims to: 1) synthesize the role currently played by ICT towards improved governance, management and accountability of urban service providers in Africa as well as other regions, 2) explore current ICT initiatives that are relevant to the World Bank's thematic concerns, 3) reconcile existing deficiencies/barriers towards potential for replication, and 4) develop a roadmap to render easy strategy implementation by project teams. Section one outlines evolving trends in urban governance and presents ICT as a potential tool in the environment of modern governance. Section two discusses the role of ICT in some of the Bank's core areas of urban focus, namely: local governance and economic development; intergovernmental fiscal relations and municipal finance; urban poverty and slum upgrading; urban planning, land and housing; urban environment and climate change; and water and sanitation service delivery. An analysis of fundamental ICT methodologies employed is discussed in section three. Section four, in conclusion, suggests an action-plan for enhancing ICT initiatives as a component of the Bank's lending activities.